Does Low Dose Steroids Confer Benefits in Sepsis and Septic Shock? (BIRDEM Medical Journal, 2017)
Over the last 40 years, the use of corticosteroids in sepsis and septic shock has evolved from the initial use of high-dose, short-duration steroid therapy in the 1980s, to the recent recommendation of using low-dose longerduration steroid therapy in refractory septic shock patients. A recent, prospective, open-label, randomized, controlled pilot trial of patients in four adult intensive care units in London-teaching hospitals showed that hydrocortisone decreased vasopressin requirements, reduced the duration and reduced the required dose, when used together in the treatment of septic shock, but it did not alter plasma vasopressin levels. The optimal dosing of hydrocortisone, about 300 mg/day, was agreed uniformly. As this dose also provides sufficient mineralocorticoid effects, the additional use of mineralocorticoid is not needed. Despite the fact that severely ill septic shock patients are given treatment, according to the current guidelines, the survival benefit is unproven. The benefits of steroids on less severely ill septic patients are still questionable. More research is highly recommended to successfully identify the benefits of steroids in septic shock.Birdem Med J 2017; 7(1): 48-59